Karakteristik Adonan dan Roti Tawar dengan Penambahan Enzim dan Asam Askorbat pada Tepung Terigu - Agus Sutriyono; Feri Kusnandar; Tjahja Muhandri (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
Wheat flour containing a 33-39% wet gluten is commonly applied in pan bread processing, however, it is expensive. The use of wheat flour containing a lower wet gluten yields a lower quality bread. This objective of this research was to produce acceptable quality pan bread using enzyme-treated wheat flour containing medium wet gluten content (31.8%). Wheat flour was treated by adding enzymes and ascorbic acid. The combination of enzymes (30 ppm α-amylase, 26 ppm α-glucosidase, 16 ppm xylanase), and 40 ppm ascorbic acid yielded dough resistancy and extensibility as well as the bread qua-lity that miccked those made of high wet gluten wheat flour (35.0%).